Why do the Chinese learners produce the expression “de fato” in Portuguese so frequently? - Sun, Yuqi (BELT - Brazilian English Language Teaching Journal, 2015)
The present paper aims to investigate why Brazilian teachers may have the impression that Chinese exchange students frequently produce the expression “de fato”(“in fact” or “actually” in English), which is not so commonly used among Brazilian speakers. The study was developed in four stages: 1) an analysis of the entries of “de fato” from Portuguese, Portuguese-English and Portuguese-Chinese dictionaries, and a review of previous linguistic studies on these words; 2) a compilation of two corpora in Portuguese, consisting of academic texts written by Brazilians and Chinese students; 3) a classification of “de fato” from a pragmatic point of view; 4) a contrastive analysis of the pragmatic strategy for using the expression in the two corpora. The results show that although Chinese learners more frequently produce the expression “de fato” in their academic texts, the different pragmatic strategies used in contextual communications may be the main reason for drawing the attention of native Portuguese speakers.